Screening and analysing toxic genes from Vibrio isolates causing acute hepatopancreatic necrosis disease in white-leg shrimp at Thua Thien Hue - Quảng, Hoàng Tấn; Lan, Trần Thúy; Thi, Phạm Thị Diễm; Nhân, Lê Thị Tuyết; Ngọc, Lê Mỹ Tiểu; Trâm, Nguyễn Duy Quỳnh; Liên, Nguyễn Thị Thu (Hue University Journal of Science: Natural Science, 2020)
Acute hepatopancreatic necrosis disease (AHPND) is a disease caused by bacteria, with the death ratio up to 100% in the population of Litopenaeus vannamei and Penaeus monodon, and causes great economic losses to many shrimp‐producing countries in Asia. Previous studies have shown that not all strains of Vibrio can cause AHPND because they contain different toxin genes, such as pirAvp, pirBvb, tlh, trh, and tdh. In this study, we evaluate the presence of several toxic genes on Vibrio isolates from Thua Thien Hue province and analyze the sequence of these genes. The results show that in 14 Vibrio strains carrying pirABvp gene, the tlh and toxR genes occur in 14/14 and 7/14 strains, respectively, while none of them have the two genes of trh and tdh. Analyzing the sequence of four DNA fragments shows that these genes have high similarity (98–100%) compared with the genes announced on the Genbank. Genes pirAvp and pirBvp are less different, while tlh and toxR genes are more different. The results could be used for further studies in the production of bioproducts for the prevention and treatment of acute hepatopancreatic necrosis disease in shrimp.